Neural correlates of the non-optimal price: an MEG/EEG study - Gorin, Aleksei; Kuznetsova, Elizaveta; Kislov, Andrew; Levchenko, Egor; Klucharev, Vasily; Moiseeva, Victoria; Yurchenko, Anna; Luzhin, Alexander; Galkina, Natalia; Shestakova, Anna N. (Frontiers in Human Neuroscience, 2025)
IntroductionSetting the right price is crucial for effectively positioning products in the market. Conversely, setting a “non-optimal price”—one that is perceived as much lower or higher than the product's true market value—can negatively influence consumer decisions and business results.MethodsWe conducted two electroencephalography (EEG) studies and one magnetoencephalography (MEG) study to investigate brain mechanisms underlying the perception of prices during a price judgment task. In each trial, participants were exposed to a mobile phone image (iPhone, Nokia, or Xiaomi) followed by a price, and instructed to judge whether the price was high or low based on a target word (“cheap” or “expensive”).ResultsIn both EEG experiments, we found a strong N400-like response to the incongruent target words following prices that substantially differed from the real market value of the mobile phone. The MEG experiment extended these findings by localizing the brain source of the price-related, M400-like response, the magnetic counterpart to the N400 component, in the ventromedial prefrontal cortex (vmPFC) and anterior cingulate cortex (ACC) implicated in value-based and reward-based learning, respectively. Our results demonstrate that both the brain sources and the timing of the price-related M400 response differed from those of the standard M400 evoked by semantically incongruent words.DiscussionOverall, our results suggest that the N400-like response can serve as a neural marker of price-product incongruity, with potential applications in consumer research.